ANALISIS PENGARUH RADIASI GELOMBANG ELEKTROMAGNETIK PADA OPERATOR DITINJAU DARI KESEHATAN DAN KESELAMATAN KERJA (K3) - Duma Pabiban; Mychael Gatriser Pae; Yustinus SB Ada; Maria D. Badjowawo; Daud Obed Bekak; Rochani; Gilang Rahdian, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
Electromagnetic radiation plays an important role in the clinical field but also poses health and safety risks to equipment operators. This study aims to determine the level of electromagnetic radiation exposure in the Radiology Unit of General Hospital X and analyze its effects on operator health. The research used a quantitative approach with data obtained from measurements using an Electromagnetic Field Tester (Geiger Muller) and questionnaires distributed to radiology operators with a Likert scale. Data validity and reliability were tested before analysis using SPSS V.26. The results showed that the use of electronic devices had no significant effect on operator health (p = 0.532 > 0.05), while operator behavior (p = 0.004 < 0.05) and the implementation of Occupational Health and Safety (K3) practices (p = 0.006 < 0.05) significantly affected health. The F-test showed a combined significant effect (p = 0.015 < 0.05). Measured exposure levels were 3.06 µT for CT Scan, 0.28 µT for X-ray, and 0.04–0.79 µT for Panoramic machines, all below the ICNIRP safety limit of 500 µT. Consistent safety practices and maintaining a minimum 2-meter operating distance are essential to reduce radiation risk